2019
DOI: 10.1371/journal.pone.0217817
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic transmission clusters among newly diagnosed antiretroviral drug-naïve patients with human immunodeficiency virus-1 in Korea: A study from 1999 to 2012

Abstract: Population-level phylogenetic patterns reflect both transmission dynamics and genetic changes, which accumulate because of selection or drift. In this study, we determined whether a longitudinally sampled dataset derived from human immunodeficiency virus (HIV)-1-infected individuals over a 14-year period (1999–2012) could shed light on the transmission processes involved in the initiation of the HIV-1 epidemic in Korea. In total, 927 sequences were acquired from 1999 to 2012; each sequence was acquired from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…When possible, sequences of the appropriate length belonging to transmission events previously identified in the literature were included in the phylogenetic analysis to verify the correct Bayesian inference [37,38].…”
Section: Phylogenetic Analyses and Transmission Clustersmentioning
confidence: 99%
“…When possible, sequences of the appropriate length belonging to transmission events previously identified in the literature were included in the phylogenetic analysis to verify the correct Bayesian inference [37,38].…”
Section: Phylogenetic Analyses and Transmission Clustersmentioning
confidence: 99%
“…Among the 876 infected individuals reported from 1985 to 1998, OSs accounted for 18.4% 1 . Previous studies have shown that 80% of patients in these groups and their partners were infected with non-B subtype viruses 5 , 6 .…”
Section: Introductionmentioning
confidence: 97%
“…The proportion of MSM was higher in younger age groups, 71.5% in 18–29 years and 92.9% in 18–19 years, respectively 3 . Currently, more than 80% of the HIV epidemic in Korea is attributed to subtype B 6 , 10 . A recent nationwide study demonstrated that subtype B was identified in 93.1% of 927 samples collected between 1999 and 2012 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, many epidemiological studies have been conducted using partial genome sequence, such as gag , pol , or env genes, and the proportion of Korean B was reported (87.3%) 7 , 24 , 25 . Several studies consistently reported this unique Korean clade B (Korean B), by analyzing various genes such as nef 24 , env 26 , vif 27 , and pol 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%